63rd Device Research Conference Digest, 2005. DRC '05. 2005
DOI: 10.1109/drc.2005.1553100
|View full text |Cite
|
Sign up to set email alerts
|

Vertical high mobility wrap-gated inas nanowire transistor

Abstract: We demonstrate a wrap-gated Field Effect Transistor based on a matrix of vertically standing InAs nanowires [1]. A lower limit of the mobility, derived from the transconductance, is on the order of 3000 cm2NVs. The narrow -100 nm channels show excellent current saturation and a threshold of Vg = -0.15 V. The sub-threshold characteristics show a close to ideal slope 157

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 4 publications
1
56
1
Order By: Relevance
“…Although, InAs nanowire devices [8][9][10][11] have higher mobility than silicon based devices, the mobility in nanowires is significantly lower than that of bulk InAs [7][8][9]12 due to a variety of factors including increased electron/hole scattering rates and surface scattering mechanisms 8 . A detailed understanding of various carrier scattering mechanisms is essential to be able to improve experimental methods to build higher performance nanowire transistors in the future.…”
mentioning
confidence: 99%
“…Although, InAs nanowire devices [8][9][10][11] have higher mobility than silicon based devices, the mobility in nanowires is significantly lower than that of bulk InAs [7][8][9]12 due to a variety of factors including increased electron/hole scattering rates and surface scattering mechanisms 8 . A detailed understanding of various carrier scattering mechanisms is essential to be able to improve experimental methods to build higher performance nanowire transistors in the future.…”
mentioning
confidence: 99%
“…Recently nanowires (NWs) have attracted attention as one of the most promising ways to combine highperformance Ⅲ-Ⅴ materials with new functionality [1][2][3][4] and existing Si technology [5,6]. An unintentional NW shell can harm device functionality by short circuiting axially designed components and by becoming a surrounding and competing recombination center [7] for charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Suk et al have shown transistor data for 10-nm lateral Si wires with a full wrap gate using SiO 2 as gate dielectric [3]. In the vertical geometry, many groups are currently working with epitaxially grown nanowires [4]- [7]. An important motivation here is the possibility of growing group III-V nanowires directly on Si, as well as highly lattice-mismatched semiconductor heterostructures within a wire [8]- [10].…”
mentioning
confidence: 99%